Conversion of industrial liquid construction waste with plasma on hydrogen. Issue 1 (April 2021) - Cucos, I; Isopescu, D N; Antonescu, I; Alecu, C I; Caunii, V; Cucos, V C; Agavriloaie, M O
Abstract: This paper presents a modern system for conversion with plasma with hydrogen of industrial liquid waste which has implemented a control system through thermoregulatory with PID control laws. Modeling and simulation of thermochemical plasma process performed using specialized software Matlab & Simulink, Ansys allows the optimum control of the temperatures and chemical reactions of the plasma reactor on hydrogen, allowing the conversion of hazardous industrial liquid waste into electrical and thermal energy and useful raw materials that can be reused in the production process.